Anisotropic schrodinger equation quantum corrections for 3D Monte Carlo simulations of nanoscale multigate transistors - Djordje Peric (2015 International Workshop on Computational Electronics (IWCE), 2015)
We incorporated anisotropic 2D Schrodinger equation based quantum corrections (SEQC) that depends on valley orientation into a 3D Finite Element (FE) Monte Carlo (MC) simulation toolbox. The MC toolbox was tested against experimental ID-VG characteristics of the 22 nm gate length GAA Si nanowire (NW) with excellent agreement at both low and high drain biases. We then scaled the Si GAA NW according to the ITRS specifications to a gate length of 10 nm. To show the effect of anisotropic QC on the ID-VG characteristics, we simulate two 8:1 nm gate length FinFETs, rectangular-like (REC) and triangular-like (TRI), with the <;100> and 〈100〉 channel orientations. The QC anisotropy effect is more pronounced in the 〈100〉 channel TRI device increasing the drain current by about 13% and slightly decreasing the current by 2% in the 〈100〉 channel REC device. However, the QC anisotropy has negligible effect in any device in the 〈100〉 orientation.